Factors explaining individual differences in taste sensitivity and taste modality recognition among Finnish adults - Sari Puputti; Heikki Aisala; Ulla Hoppu; Mari Sandell (Blackwell Publishing Ltd, 2025)
The objective of this study was to investigate the factors affecting interindividual variation in the sense of taste among Finnish adults. Two components of taste function were examined with five established taste modalities: taste sensitivity and capability to identify taste modalities. The potential explanatory factors for taste function included gender, age, BMI, and smoking. In total, 205 volunteers participated in the study at the sensory evaluation laboratory of Functional Foods Forum. Older age (>50 years) and male gender predicted a less sensitive sense of taste in general. For umami sensitivity, high BMI along with older age predicted lower sensitivity. Additionally, taste recognition and sensitivity were related in bitter and umami tastes. Older age was also associated with a poorer capability in taste recognition. Sour–bitter, umami–salty, and salty–umami were the most frequent taste confusions.